A study on factors causing stress among doctors - SHREE, MS. K.C. RAJA; ALAGESAN, MS. SHARMILA (The journal of contemporary issues in business and government, 2020)
Work stress can affect doctors physical and mental health by reducing their efficiency and having a pessimistic effect on their quality of life. Stress among doctors is a synergy between the challenging nature of their work and committed personality .Doctors are having a highly demanding nature of work ,both the lack of control and inadequate rewarding systems in the workplace making doctors stressful. Handling unexpected responsibilities may increase the Stress. Work stress can be induced by various factors such as excessive workload and extended work hours to handle critical cases and serious working environments..work stress will also cause a negative impact on their family life . Many factors can enhance stress , including low career growth, lack of managerial relationship with staff, poor working environment and prolonged working hours. Innovation should be implemented in order to reduce work stress among doctors.